2017
DOI: 10.1042/bsr20170886
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen deprivation aggravates cardiac hypertrophy in nonobese Type 2 diabetic Goto–Kakizaki (GK) rats

Abstract: Both Type 2 diabetes mellitus (T2DM) and estrogen deprivation have been shown to be associated with the development of cardiovascular disease and adverse cardiac remodeling. However, the role of estrogen deprivation on adverse cardiac remodeling in nonobese T2DM rats has not been clearly elucidated. We hypothesized that estrogen-deprivation aggravates adverse cardiac remodeling in Goto–Kakizaki (GK) rats. Wild-type (WT) and GK rats at the age of 9 months old were divided into two subgroups to have either a sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 53 publications
2
9
0
Order By: Relevance
“…As expected, these rats exhibited a marked decrease in uterine weight at 4 mo post-OVX, i.e., 0.56 Ϯ 0.20 g Sham-WT vs. 0.14 Ϯ 0.02 g OVX-WT (P Ͻ 0.05; n ϭ 10/group) and 0.58 Ϯ 0.05 g Sham-GK vs. 0.18 Ϯ 0.02 g OVX-GK (P Ͻ 0.05; n ϭ 10/group). This change in the reproductive system was consistent with the deterioration of ovarian function associated with OVX and thus inducing estrogen deficiency in these rats, as reported previously (3). Having established the OVX models, we then focused on the changes in calcium and bone metabolism.…”
Section: Combined Effects Of Estrogen Deficiency and T2dm Led To Inappropriately Low Plasma Levels Of Calciotropic Hormonessupporting
confidence: 86%
See 2 more Smart Citations
“…As expected, these rats exhibited a marked decrease in uterine weight at 4 mo post-OVX, i.e., 0.56 Ϯ 0.20 g Sham-WT vs. 0.14 Ϯ 0.02 g OVX-WT (P Ͻ 0.05; n ϭ 10/group) and 0.58 Ϯ 0.05 g Sham-GK vs. 0.18 Ϯ 0.02 g OVX-GK (P Ͻ 0.05; n ϭ 10/group). This change in the reproductive system was consistent with the deterioration of ovarian function associated with OVX and thus inducing estrogen deficiency in these rats, as reported previously (3). Having established the OVX models, we then focused on the changes in calcium and bone metabolism.…”
Section: Combined Effects Of Estrogen Deficiency and T2dm Led To Inappropriately Low Plasma Levels Of Calciotropic Hormonessupporting
confidence: 86%
“…At 9 mo old, WT and GK rats were subdivided into sham-operated (Sham-WT; n ϭ 10, Sham-GK; n ϭ 10) and ovariectomized groups (OVX-WT; n ϭ 10, OVX-GK; n ϭ 10). The circulating levels of estradiol in Sham-WT, Sham-GK, OVX-WT, and OVX-GK have been reported to be 48.6 Ϯ 9.2, 49.6 Ϯ 3.7, 26.6 Ϯ 2.6, and 30.1 Ϯ 2.1 pg/mL, respectively (3). Four months after surgery (at 13 mo old), the animals were subcutaneously injected with two separate doses of calcein (10 mg/kg body wt) on day 7 and 1 before euthanasia.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that there was no significant difference between the combined and the E2+Veh groups, it can also be concluded that P4 in combination with E2 eliminates the beneficial effects of E2 on insulin resistance. Evidence suggests that reduction of E2 along with T2D causes an increase in dysfunction of beta-pancreatic cells [ 29 ], and in humans similar to rodents, the loss of E2 results in metabolic imbalances [ 30 ]. P4 has been shown to cause insulin resistance [ 31 ] and reduce insulin sensitivity in gestational diabetes by reducing the expression of glucose transporter 4 (GLUT4) in muscle and fat tissues [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This hormone is a protective factor for the cardiovascular system, and such concept has already been evidenced in some previously published papers. [21][22][23] Nonetheless, some authors suggested that the decrease in the diameter of the left ventricle in female animals under supraphysiological doses of the AAS could be due to an increase in the left ventricular wall, leading to a decrease in the ventricular chamber volume with consequent hypertension, resulting in heart failure and left ventricular hypertrophy. 24,25 Another hypothesis that would lead to an increase of muscle mass in females would be based on the same reason observed by Hayward et al, 26 who administered AAS to women and consequently observed an increase in cardiac muscle mass.…”
Section: Discussionmentioning
confidence: 99%